POTRET KESEHARIAN JAMAAH TAREKAT DAN MASYARAKAT AWAM DALAM MENERAPKAN 4 KONSEP SPIRITUAL (TAUBAT, ZUHUD, IKHLAS DAN WARA’) - Riswaty Nurazizah; Hilman Taufiq Abdillah; Aceng Kosasih (NIHAYAH: Journal of Islamic Studies, 2026)
This study examines the everyday implementation of four core spiritual concepts in Islamic mysticism repentance (taubat), asceticism (zuhud), sincerity (ikhlas), and cautious piety (wara’) among Sufi order adherents (Jamaah Tarekat) and the general Muslim community. Although these concepts are well established in classical Sufi literature, their practical meanings and applications vary across social contexts. This research aims to analyze how both groups understand, practice, and experience these concepts in daily life. Using a qualitative approach with a multi-site case study design, data were collected through non-participant observation and in-depth semi-structured interviews with ten purposively selected participants, including students, religious teachers, and community members. Data were analyzed through within-site and cross-site thematic analysis. The findings reveal that both groups share a common conceptual understanding of the four spiritual values; however, differences emerge in depth and structure of practice. Jamaah Tarekat tend to internalize taubat, zuhud, ikhlas, and wara’ through systematic spiritual discipline, guidance of a spiritual master, and structured rituals, while the general community practices these values in a more flexible and pragmatic manner integrated with everyday responsibilities. The study concludes that both patterns represent complementary forms of contemporary Islamic spirituality, reflecting a continuum between normative Sufism and neo-Sufism. These findings highlight the relevance of contextualized spiritual education to strengthen ethical character and spiritual resilience in modern Muslim society.